Maize/soybean strip intercropping produces higher crop yields and saves water under semi-arid conditions - Raza, Muhammad Ali; Yasin, Hassan Shehryar; Gul, Hina; Qin, Ruijun; Mohi Ud Din, Atta; Khalid, Muhammad Hayder Bin; Hussain, Sajad; Gitari, Harun; Saeed, Amjed; Wang, Jun; Rezaei-Chiyaneh, Esmaeil; Sabagh, Ayman El; et al. (Frontiers in Plant Science, 2022)
Sustainable increases in crop production require efficient use of resources, and intercropping can improve water use efficiency and land productivity at reduced inputs. Thus, in a three-year field experiment, the performance of maize/soybean strip intercropping system differing with maize plant density (6 maize plants m-2, low, D1; 8 maize plants m-2, medium, D2; and 10 maize plants m-2, high, D3) was evaluated in comparison with sole maize or soybean cropping system. Results revealed that among all intercropping treatments, D2 had a significantly higher total leaf area index (maize LAI + soybean LAI; 8.2), total dry matter production (maize dry matter + soybean dry matter; 361.5 g plant-1), and total grain yield (maize grain yield + soybean grain yield; 10122.5 kg ha-1) than D1 and D3, and also higher than sole maize (4.8, 338.7 g plant-1, and 9553.7 kg ha-1) and sole soybean (4.6, 64.8 g plant-1, and 1559.5 kg ha-1). The intercropped maize was more efficient in utilizing the radiation and water, with a radiation use efficiency of 3.5, 5.2, and 4.3 g MJ-1 and water use efficiency of 14.3, 16.2, and 13.3 kg ha-1 mm-1, while that of intercropped soybean was 2.5, 2.1, and 1.8 g MJ-1 and 2.1, 1.9, and 1.5 kg ha-1 mm-1 in D1, D2, and D3, respectively. In intercropping, the land and water equivalent ratios ranged from 1.22 to 1.55, demonstrating that it is a sustainable strategy to improve land and water use efficiencies; this maximization is likely associated with the species complementarities for radiation, water, and land in time and space, which resulted in part from competition avoidance responses that maximize the economic profit (e. g., 1300 US $ ha-1 in D2) over sole maize (798 US $ ha-1) or sole soybean (703 US $ ha-1). Overall, these results indicate that optimizing strip intercropping systems can save 20–50% of water and land, especially under the present scenario of limited resources and climate change. However, further research is required to fully understand the resource capture mechanisms of intercrops in intercropping.